2024
DOI: 10.1021/jasms.4c00049
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Unique Fragmentation Patterns of Fentanyl Analog Protomers Using Structures for Lossless Ion Manipulations Ion Mobility-Orbitrap Mass Spectrometry

Adam L. Hollerbach,
Yehia M. Ibrahim,
Vivian S. Lin
et al.

Abstract: The opioid crisis in the United States is being fueled by the rapid emergence of new fentanyl analogs and precursors that can elude traditional library-based screening methods, which require data from known reference compounds. Since reference compounds are unavailable for new fentanyl analogs, we examined if fentanyls (fentanyl + fentanyl analogs) could be identified in a reference-free manner using a combination of electrospray ionization (ESI), highresolution ion mobility (IM) spectrometry, high-resolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…It is not entirely unexpected that the intensities of the two IM distributions of nitazenes depends on the presence of water in the ESI solvent, though the extent to which a nitro group affects the signal intensities of the two IMS distributions was surprising. Hollerbach et al recently demonstrated that fentanyls (fentanyl + fentanyl analogs) also exhibit two gas-phase protomers whose two IMS distributions depend on the water concentration in the ESI solvent . However, previously observations showed that water caused the second IMS distributions of fentanyls to exhibit higher signal intensities compared to the first.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is not entirely unexpected that the intensities of the two IM distributions of nitazenes depends on the presence of water in the ESI solvent, though the extent to which a nitro group affects the signal intensities of the two IMS distributions was surprising. Hollerbach et al recently demonstrated that fentanyls (fentanyl + fentanyl analogs) also exhibit two gas-phase protomers whose two IMS distributions depend on the water concentration in the ESI solvent . However, previously observations showed that water caused the second IMS distributions of fentanyls to exhibit higher signal intensities compared to the first.…”
Section: Resultsmentioning
confidence: 99%
“…Since all fourteen nitazenes exhibited at least two IMS distributions, an explorative study was performed to determine the cause of these two peaks, such as them being rotational conformers (rotomers), protonation site specific conformers (protomers), or another type of gas-phase conformer. In a previous study involving fentanyl and fentanyl analogs, Hollerbach et al examined how the concentration of water in the ESI solvent affected the IMS distributions and noticed large differences in the intensity ratios of the two IM distributions that all fentanyls exhibited . The same logic was used in this study and the fourteen nitazenes (and five TAAs) were prepared in a mixture of 1:1 methanol:water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…10–16 This powerful technique has seen increased utility in clinical, forensic, and toxicological applications. Our group has reported on a recently commercialized high-resolution IM platform, Structures for Lossless Ion Manipulations (SLIM), 17–19 for the rapid differentiation of synthetic cannabinoid isomers. 20…”
mentioning
confidence: 99%